AESTHETICS, EDUCATION AND SOCIALISM FROM 21ST CENTURY - René Estévez, Pablo (Atenas, 2013)
This proposal constitutes a synthesis of three fundamental themes I have treated in recent years; namely, the place of aesthetics in the comprehensive development of the personality; the aesthetic sustainability as a principle of social and human development (particularly under socialism), and the upgrading of educators as main actors in the bettering of the educational praxis. The paper assumes the primal meaning of Aisthesis (the ¨aesthesia¨ and the ¨aesthetics¨) as the matrix for the socio-philosophical analysis of such topics, which are defined synthetically as four key concepts: aesthetic education, human development, aesthetic sustainability and XXI Century Socialism, and emphasizes on its role in the understanding of the soio-environmental problems that affect the contemporary society, and in the design of strategies for the bettering of Cuban education